2006
DOI: 10.1088/0031-9155/52/2/005
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishability for magnetic resonance–electrical impedance tomography (MR–EIT)

Abstract: A distinguishability measure is defined for magnetic resonance-electrical impedance tomography (MR-EIT) based on magnetic flux density measurements. This general definition is valid for 2D and 3D structures of any shape. As a specific case, a 2D cylindrical body with concentric inhomogeneity is considered and a bound of the distinguishability is analytically formulated. Distinguishabilities obtained with potential and magnetic flux density measurements are compared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In both studies, optimum coil current patterns are found by maximizing the distinguishability function. Altunel et al (2007) further utilize the distinguishability concept in MREIT. They expressed the distinguishability of MREIT as a function of magnetic flux density measurements for a conductivity distribution with a concentric inhomogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…In both studies, optimum coil current patterns are found by maximizing the distinguishability function. Altunel et al (2007) further utilize the distinguishability concept in MREIT. They expressed the distinguishability of MREIT as a function of magnetic flux density measurements for a conductivity distribution with a concentric inhomogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, current density distribution of wplane is known [8]. Thus relation between current density distributions of v and w-planes should be found.…”
Section: B 2-d Cylindrical Body With Eccentric Inhomogeneitymentioning
confidence: 99%
“…Consider conductivity distributions Based on distinguishability definition in [8], total distinguishability is the sum of differences between magnetic flux densities at all points.…”
Section: A 2-d Cylindrical Body With Concentric Inhomogeneitymentioning
confidence: 99%
See 1 more Smart Citation